Solvent Extraction of Iron from Aluminium Sulphate Leach Solution Using Acetylacetone-Chloroform - KARIMI, HAJIR; GHEADI, MEHRORANG (Asian Journal of Chemistry, 2010)
The purified aluminium sulphate which contains important Al compounds has been used in paper milling industry and water purification. This work is focused on the extraction of iron from aluminium sulphate leach solution by acetylacetone-chloroform as leaching agent. The results showed that iron can be efficiently extracted from leach solution in short time. The influence of effective variables including acidity, temperature, type and concentration of extracting solvent, aqueous to organic phase ratio (enrichment factor) and kind of diluents were investigated. The optimum extraction condition has been set as follow: pH 2.57, temperature 40ºC, phase ratio of 1:1 and solvent concentration of 0.6 M. The unique advantage of the present work relative to other reported method is the higher extraction efficiency and lower cost.